Teachers' views on the fulfillment level of learning attainments on information technologies in the life science courses - Semerci, Cetin; Semerci, Nuriye; Duman, Burcu (Sila Science, 2012)
The aim of this research is to determine teachers' views on the fulfillment level of learning attainments on information technologies in the Life Science Courses. Survey method was used in the present study. The study population is classroom teachers who teach in the 2nd, 3rd and 4th grades of primary schools in Elazig city center in Turkey. The sample of the study comprises of 346 classroom teachers. Data were collected by means of a questionnaire which was prepared to determine the opinions of teachers concerning the fulfillment levels of learning attainments. The result can be interpreted as being due to new teachers being more interested in technologies in accordance with age and consciously more perfectionist than teachers with higher seniority.
Keywords: Learning attainments; Life science courses; Information technology